Answer:
26V + 2
Step-by-step explanation:
This is the same as saying f(g(x)), where x = 26
First, lets figure out what g(x) is equal to when x = 26
g(26) = V(26) - 1 = 26V - 1
Now we input 26V - 1 into f(x) for x
f(26V-1) = (26V-1) + 3 = 26V + 2
Answer:
0.85
Step-by-step explanation:
Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identity
tanx = ![\frac{1}{cotx}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bcotx%7D)
Consider the left side
← divide terms on numerator/denominator by cotA
= ![\frac{\frac{cotA}{cotA}-\frac{1}{cotA} }{\frac{cotA}{cotA}+\frac{1}{cotA} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7BcotA%7D%7BcotA%7D-%5Cfrac%7B1%7D%7BcotA%7D%20%20%7D%7B%5Cfrac%7BcotA%7D%7BcotA%7D%2B%5Cfrac%7B1%7D%7BcotA%7D%20%20%7D)
= ![\frac{1-tanA}{1+tanA}](https://tex.z-dn.net/?f=%5Cfrac%7B1-tanA%7D%7B1%2BtanA%7D)
= right side , thus proven
83°?
- SS postulate, 2 sides of triangle r equal, meaning 3rd is most likely equal I think.
- so all angles r equal
- all interior angles r congruent. so r exterior
180 - 97 = 83
Answer:
B: Each sandwich has one third pound of ham.